The Patterning of Obsessive Love in Cecelia Ahern’s P.S. I Love You - Chishty, Mahtab; Ajmal, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
This study proposes that human beings display three types of emotions in intimate relationships: 1) the sex drive or lust 2) attraction 3) attachment, accompanied in humans by feelings of calm, comfort and emotional union with the mate. So, this study offers reading of Cecelia Ahern’s P.S. I Love You. She has depicted the concept of love in a different and unique way. This study is contextualized within the textual analysis of P.S. I Love You by Ahern in order to explore and analyze the ways in which love is different from previous eras as compared to the twenty first century. In order to highlight and expose the different forms of love, the concept of marriage and friendship in regard to modernization and to find out the major differences among love, friendship and infatuation. The critical analysis reveals that love nowadays has been seen in myriad of forms and ways and every individual considers himself/herself on the right track irrespective of opinion given by others around him or her.